RpuS/R Is a Novel Two-Component Signal Transduction System That Regulates the Expression of the Pyruvate Symporter MctP in Sinorhizobium fredii NGR234 - Ramos, Ana Laura; Aquino, Maria; García, Gema; Gaspar, Miriam; de la Cruz, Cristina; Saavedra-Flores, Anaid; Brom, Susana; Cervantes-Rivera, Ramón; Galindo-Sánchez, Clara Elizabeth; Hernandez, Rufina; Puhar, Andrea; Lupas, Andrei N.; et al. (Frontiers in Microbiology, 2022)
The SLC5/STAC histidine kinases comprise a recently identified family of sensor proteins in two-component signal transduction systems (TCSTS), in which the signaling domain is fused to an SLC5 solute symporter domain through a STAC domain. Only two members of this family have been characterized experimentally, the CrbS/R system that regulates acetate utilization in Vibrio and Pseudomonas, and the CbrA/B system that regulates the utilization of histidine in Pseudomonas and Azotobacter. In an attempt to expand the characterized members of this family beyond the Gammaproteobacteria, we identified two putative TCSTS in the Alphaproteobacterium Sinorhizobium fredii NGR234 whose sensor histidine kinases belong to the SLC5/STAC family. Through the characterization of different mutants, we were able to identify the first one TCSTS as a CrbS/R homolog that is also needed for growth on acetate, while the second one TCSTS, RpuS/R, is a novel system required for optimal growth on pyruvate. Using RNAseq and transcriptional fusions, we determined that in S. fredii the RpuS/R system up-regulates the expression of an operon coding for the pyruvate symporter MctP when pyruvate is the sole carbon source. In addition, we identified a conserved DNA sequence motif in the putative promoter region of the mctP operon that is essential for the RpuR-mediated transcriptional activation of genes under pyruvate-utilizing conditions. Finally, we show that S. fredii mutants lacking these TCSTS are affected in nodulation, producing fewer nodules than the WT strain and at a slower rate.